Penerapan Sistem Manajemen Keperawatan Untuk Meningkatkan Keselamatan Pasien Anak - Nurnainah Nurnainah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Background: Pediatric patient safety is a top priority in healthcare because children are highly vulnerable to medical errors and at risk of injury during care. An effective nursing management system is believed to improve the quality of care and reduce patient safety incidents. Objective: This study aims to analyze the application of a nursing management system to improve pediatric patient safety. Methods: The study used a descriptive approach with a literature review and observational method limited to pediatric care units. Data were obtained from national and international journals, nursing textbooks, and patient safety guidelines. Results: The study results indicate that the implementation of a nursing management system, which includes care planning, staff organization, implementation of standard operating procedures, and ongoing evaluation, can improve nurses' adherence to pediatric patient safety principles. Conclusion: The nursing management system plays a crucial role in improving pediatric patient safety and needs to be consistently implemented in nursing practice.